NDVI, crescimento e produtividade de cultivares de trigo submetidas a doses de nitrogênio - Rissini, Adriano Luiz Lodi (2011)
The nitrogen (N) is one of the most important elements for plants development and highly unstable in soil. Variables such as dry matter (DM) and amount of chlorophyll on leaves, are important components in the plant, which, when measured during development, can be used to estimate the production potential, which can be used in quantification of N rate to be applied. Remote sensing techniques, using reflectance data of incident, electromagnetic waves on the crop canopy, can assist the quantification of these variables. In this sense, the objective of this study was to evaluate the use of NDVI as a tool for estimating the productivity of wheat cultivars under doses of N. The experiment was conducted in Guarapuava - PR. The experimental design was random blocks and followed a 4x5 factorial design with four cultivars and five N rates. The evaluations were done in the NDVI readings obtained by passive and active sensor, DM of the aerial part at the phenological stages Feeks 3, 8 and 10.5.1, foliar N content and productivity. Data were subjected to analysis of variance and Tukey test at 5% significance. Regression analysis and Pearson correlation significance at 1% were also done. It was found significant differences in the readings of cultivars in NDVI for each N rate and phenological stage in both sensors. Results of determination coefficients higher than 0.85 and 0.81 for DM and NDVI, 0.70 and 0.71 for foliar content N and NDVI, 0.92 and 0.90 for NDVI and productivity were found respectively for passive and active sensor in cultivars. It was possible to generate a model to estimate productivity in the early stages in the culture development. Significant differences between the sensors, for NDVI readings were found in all cultivars and phenological stages. However, the passive sensor, even dependent on solar radiation, was efficient in obtaining NDVI data compared to the active sensor, obtaining values of Pearson correlation higher than 0.97.